Pemanfaatan Limbah Styrofoam Sebagai Bahan Tambah Terhadap Karakteristik Campuran Aspal Buton Tipe CPHMA Dengan Perendaman Berulang - Dedi Arham Al Anzari; Abd. Rahim Nurdin; Nurhadijah Yunianti (Program Studi Teknik Sipil Universitas Bosowa, 2023)
Cold Paving Hot Mix Asbuton is a mixture of asbuton consisting of aggregate, granular asbuton, rejuvenator and other added ingredients mixed with cold heat. Hot and cold mixed asphalt asphalt is a ready-to-use asphalt mixture product that is used as a pavement surface layer for low traffic volume roads. The purpose of this study was to obtain the effect of adding styrofoam to the Marshall characteristics of the CPHMA type Buton asphalt mixture with repeated immersion. This study uses styrofoam waste with the addition of 5%, 10%, and 15%. Samples of test objects made as many as 33 samples, 6 normal samples and 27 samples of variation. Treatment of the specimens was carried out with repeated immersion variations of 6, 12, and 18 days. The manufacture of test objects is hot mixed and refers to the 2018 Bina Marga Specifications, the test is carried out with the Marshall test equipment. The results of this test indicate that the effect of Styrofoam waste as an additive in the CPHMA type Buton asphalt mixture with repeated immersion can cause the value of density, stability, MQ, and VFB to decrease. While the value of flow, VMA, and VIM increased